Empowering Midwives and Obstetric Nurses - Ray, Amita (IntechOpen, 2021)
Empowering Midwives and Obstetric Nurses is a practical approach to understanding the health of women and newborns. It supports learning and prepares readers for the challenges faced in contemporary midwifery healthcare. Written by experts in the field, this book provides an overview, highlights important features, and brings to light certain contemporary issues pertaining to the science and art of midwifery.